Development of an approach to mathematical description of imbalance in methabolic processes for its application in the medical diagnostic information system - Dobrorodnia, H.; Vуsotska, O.; Georgiyants, M.; Balym, Y.; Rak, L.; Kolesnikova, O.; Levykin, V.; Dovnar, O.; Nosov, K.; Porvan, A. (Eastern european jornal of enterprise technologies, 2018)
The problem of diagnosing the metabolic syndrome associated with disturbance of carbohydrate and lipid metabolism was considered in this work. A new approach to determination of imbalance of metabolic processes was proposed. It is based on combining of the flow cultivator and the Lotka-Volterra models. Application of the model of flow cultivator provides an opportunity for objective assessment of initial conditions of behavior of the system acting as a human body and enables time matching of the model basic parameters. Initial conditions for modeling metabolic processes were determined using the Lotka-Volterra model. Use of these conditions makes it possible to determine stability of metabolic processes taking into account individual values of waist and hip circumference, weight, heart rate, age, systolic and diastolic pressure and the calculated Harris-Benedict value. Cross-checking for a possible development of metabolic processes in people with normal and impaired metabolism has shown that the developed approach can be used in medical institutions for the early diagnosis of metabolic disorders. To establish balance of the metabolic processes that are characteristic of people without and with metabolic disorders, retrospective data of examination of 155 young people who were under observation for several years at Kharkiv municipal clinical hospital No. 11, Ukraine, have been analyzed. The proposed approach is the basis of mathematical support of the medical diagnostic information system for detecting imbalance of metabolic processes which is developed currently. Application of such a system in the future will make it possible to study in detail the influence of various gender, territorial and age characteristics on the balance of metabolic processes in the human body.
Keywords: Flow cultivator; Lotka-Volterra model; metabolic syndrome; balance